Wheat blast: quantitative pathway analyses for the Triticum pathotype of Magnaporthe oryzae and phenotypic reaction of U.S. wheat cultivars - Cruz, Christian D. (Kansas State University, 2013)
Wheat blast, caused by the Triticum pathotype of Magnaporthe oryzae (MoT), is a serious disease of wheat causing yield failures and significant economic losses during epidemic years in Brazil, Paraguay, and Bolivia. Although outbreaks occur only sporadically, wheat blast is considered a major disease affecting wheat production in South America and may be a threat to the wheat crop in the United States. Wheat is a major crop in the U.S. and wheat exports from the U.S. are important to food security of several countries around the World. Thus, it is important to understand the potential for MoT entry and establishment into the U.S. and to test U.S. wheat cultivars for susceptibility to MoT. The hypotheses of this research project were a) importing wheat grain from Brazil does not pose a risk for MoT establishment in the U.S., and b) resistance to MoT head infection does not exist in U.S. hard red winter wheat elite cultivars. Quantitative pathway analysis models were used to estimate the risk of MoT entry and establishment, in the coterminous U.S. and in a more targeted area within southeast North Carolina, via the importation of wheat grain from Brazil. The pathway model predicted that significant risk for MoT entry and establishment exists in some areas of the U.S. However, in approximately 60% of the coterminous U.S. winter wheat production areas the risk of MoT establishment was estimated to be zero. With respect to winter wheat growing areas in the U.S., conditions for MoT establishment and wheat blast outbreak occur only in small, restricted geographic areas. A higher resolution pathway analysis based on a ground transportation corridor in North Carolina indicated that conditions for MoT establishment exist seven out of ten years. Among U.S. cultivars tested, a continuum in severity to head blast was observed; cultivars Everest and Karl 92 were highly susceptible with more than 90% disease severity, while cultivars PostRock, Jackpot, Overley, Jagalene, Jagger, and Santa Fe showed less than 3% infection.
Keywords: Magnaporthe oryzae; Wheat blast; Brusone trigo; Pathway analysis; Disease Phenotype; Pest risk analysis; Epidemiology (0766); Plant Pathology (0480)